First-Line Interactive Wound Dressing Update: A Comprehensive Review of the Evidence - Weller, Carolina D.; Team, Victoria; Sussman, Geoffrey (Frontiers in Pharmacology, 2020)
Wound management is a significant and growing issue worldwide. Knowledge of dressing products and properties and clinical expertise in dressing selection skills are two major components in holistic wound care to ensure evidence-based wound care. With expanding global market of dressing products, there is need to update clinician knowledge and skills in wound care. Optimum wound management depends on clinicians’ understanding of the wound healing process and their knowledge of the properties of available dressings. We conducted a comprehensive literature review and discuss physical properties, forms and products, advantages and disadvantages, and indications and contraindications and effectiveness of first-line interactive/bioactive dressing groups commonly used in clinical practice. These include semi-permeable films, foams, hydroactives, alginates, hydrofibres, hydrocolloids, and hydrogels. In making decisions regarding dressing product selection, clinicians should consider patient and wound assessment, and dressing properties and dressing cost and use wound management guidelines to ensure optimum patient outcomes.